Pengembangan Media Flashcard Berbasis Augmented reality untuk Meningkatkan Kemampuan Pemecahan Masalah Pecahan Kelas IV - Putra, Susetya Dwi; Andrijati, Noening; Nurharini, Atip (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research aims to develop and evaluate the feasibility, practicality, and effectiveness of augmented reality-based flashcard media in enhancing students' problem-solving skills in fractions. Utilizing the Plomp development model, the study was conducted during the second semester of the 2024/2025 academic year in four public elementary schools in the Wijayakusuma cluster, Semarang City. A pretest-posttest control group design with simple random sampling was employed. The problem-solving ability test was aligned with Polya's indicators. The findings indicate that the augmented reality-based flashcard media is highly feasible, achieving an average feasibility score of 92.98%. Assessments based on media validation, material validation, and practicality all fell into the very feasible category. The practicality test yielded a score of 91.52% from both teachers' and students' responses, indicating high practicality. Effectiveness testing through pretests and posttests showed significant improvement in problem-solving abilities, with a significance value of 0.000 in the t-Test. N-Gain analysis revealed that the flashcard media was more effective than conventional learning, with a control class N-Gain of 0.5796 and an experimental class N-Gain of 0.7090. In conclusion, augmented reality-based flashcard media effectively enhances students' mathematical problem-solving skills in fractions and serves as an alternative solution to improve the quality of fourth-grade learning.